Association of Hepcidin levels in Type 2 Diabetes Mellitus treated with metformin or combined anti-diabetic agents in Pakistani population - Tabinda Najeeb; Mohammad Saleh Soomro (late); Asher Fawwad; Nazish Waris; Ruqaya Nangrejo; Iftikhar Ahmed Siddiqui; Qamar Aziz; Abdul Basit (Journal of the Pakistan Medical Association, 2023)
Objective: To evaluate the impact of hepcidin and ferritin in pathogenesis and prognosis of type 2 diabetes mellitus subjects taking only metformin or combined anti-glycaemic agents. Methods: The observational case-control study was conducted at the Department of Physiology, Baqai Medical University, Karachi, from August 2019 to October 2020, and comprised subjects from both genders who categorised into equal groups as non-diabetic controls, newly-diagnosed type 2 diabetes mellitus patients without any treatment, type 2 diabetes mellitus patients with exposure to metformin only, type 2 diabetes mellitus patients taking oral hypoglycaemic agents along with metformin, type 2 diabetes mellitus patients taking only insulin, and type 2 diabetes mellitus patients taking insulin and oral hypoglycaemic agents. Fasting plasma glucose was determined using glucose oxidase-peroxidase method, glycated haemoglobin by high performance liquid chromatography, high-density lipoprotein and low-density lipoprotein by direct methods, cholesterol by cholesterol oxidase phenol 4-amino antipyrine peroxidase and triglycerides by glycerol phosphate oxidase-phenol 4-amino antipyrine peroxidase method. Serum levels of ferritin, insulin and hepcidin were evaluated using Enzyme-linked immunosorbent assay. Insulin resistance was assessed using homeostasis model assessment for insulin resistance. Data was analysed using SPSS 21. Results: Of the 300 subjects, there were 50(16.66%) in each of the 6 groups. Overall, there were 144(48%) males and 155(51.66%) females. The mean age was significantly lower in the control group 34.72±7.87 compared to all the diabetic groups (p<0.05), and the same was the case with respect to all the parameters (p<0.05) except high-density lipoprotein (p>0.05). Besides, hepcidin level was significantly higher in the control group (p<0.05). Ferritin levels were significantly increased in newly-diagnosed T2DM subjects compared to the controls (p<0.05) while all other groups showed decreased ferritin levels (p<0.05). Hepcidin gave inverse correlation with glycated haemoglobin only in diabetics taking only metformin (r = -0.27, p=0.05). Conclusion: Anti-diabetes drugs not only addressed type 2 diabetes mellitus, but also reduced levels of ferritin and hepcidin that are found to play a role in diabetes development. Key Words: Ferritin, Hepcidin, Insulin, Oral hypoglycaemic agents, T2DM.